Nutrant Android Application Development for Individual Nutritional Assessment: An Addie Model Approach - Al Rahmad, Agus Hendra; Mulyani, Nunung Sri; Hadi, Abdul; Azhari, Azhari (Politeknik Kesehatan Kemenkes Mamuju, 2025)
To enhance both community and clinical nutrition reporting, it is crucial for nutritionists to stay informed about technological advancements that improve the understanding of nutritional needs and the assessment of individual nutritional status, thereby supporting effective monitoring of dietary intake. This research focuses on the development and evaluation of NutrAnt, an Android-based application designed for individual nutrition assessment. Conducted in Banda Aceh City and Aceh Besar between April and July 2025, the study involved 53 nutritionists and experts selected purposively. The Research and Development (R&D) method was applied using the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The app underwent black-box and usability testing, with the analysis carried out through three stages: data reduction, data display, and conclusion drawing. To assess user satisfaction, the Technology Acceptance Model (TAM) was employed. Findings revealed that the app’s functionality was highly rated, with satisfaction scores of 85.5% from Health Office nutritionists and 90.0% from the nutritionist team. NutrAnt demonstrated its effectiveness in improving nutritionists’ ability to evaluate patients’ nutritional needs across both community and clinical settings. In conclusion, the development of NutrAnt confirmed its usability and functionality for personalized nutrition assessment. Featuring four modules, the app offers an efficient tool to support nutritionists in providing accurate nutrition services. Future developments should explore expanding the app’s features and adapting it for broader use, marking a significant step forward in advancing digital tools for nutrition assessment and reporting.